Disorganization - Blanchard, O.; Kremer, M. (Quarterly Journal of Economics, 1997)
Under central planning, many firms relied on a single supplier for critical inputs. Transition has led to decentralized bargaining between suppliers and buyers. Under incomplete contracts or asymmetric information, bargaining may inefficiently break down, and if chains of production link many specialized producers, output will decline sharply. Mechanisms that mitigate these problems in the West, such as reputation, can only play a limited role in transition. The empirical evidence suggests that output has fallen farthest for the goods with the most complex production process, and that disorganization has been more important in the former Soviet Union than in Central Europe.